A carbide-free precipitation hardened bainitic plastic mold steel and a method of manufacturing the same

CN122979758APending Publication Date: 2026-10-27福建青拓特钢技术研究有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611485957.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]综上所述,上述各专利公开的时效硬化型塑料模具钢,依旧含有较高的Mo、Ni、Al等元素,不仅合金成本高,还因为Al元素的加入,极易形成氧化铝和氮化铝的夹杂物,该类夹杂物极易在抛光过程剥落,并划伤基体

Benefits of technology

1.本发明采用低碳(C:0.05~0.15%)、极低钒(V<0.05%)的成分设计。可从源头上抑制碳化物析出,再配合热轧后水雾冷却工艺抑制了高温下的碳化物析出。从而消除碳化物与基体形成的微电偶腐蚀源,也消除了因碳化物导致抛光性能下降的负面影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979758A_ABST
    Figure CN122979758A_ABST
Patent Text Reader

Abstract

The application discloses a carbide-free precipitation hardening bainite plastic die steel and a manufacturing method thereof, and the steel contains the following components in percentage by mass: C 0.05-0.15%, Si 0.25-1.0%, Mn 0.8-2.0%, P≤0.04%, S≤0.02%, Cr 2.5-5%, Ni 0.8-2%, Cu 1-3%, Al<0.010%, and the balance of Fe and inevitable impurities, and the steel satisfies the following conditions: aging hardening index AH: 12≤AHI≤20, and Cu precipitation index CuPI≥0.9. The die steel has the following properties: tensile strength≥1100MPa, finished product hardness 37-43HRC, cross-section hardness difference of 15-300mm-thick steel plate≤2HRC, 12000-mesh polishing roughness Ra≤0.010μm, and B-type inclusions≤1.0 grade. The die steel can be used in the fields of optical grade, super-high-precision aerospace, medical treatment and precision electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mold steel, and in particular to a carbide-free precipitation-hardening bainitic plastic mold steel and its manufacturing method. Background Technology

[0002] In recent years, with rapid economic development, the upgrading of various plastic products has accelerated, and they are widely used in various industries, which has greatly promoted the rapid development of plastic mold steel. Among them, the NAK80 age-precipitation-hardening plastic mold steel developed by Daido Steel Corporation of Japan contains approximately 3.0% Ni, 1.0% Al, and 1.0% Cu. After quenching and aging treatment, Ni3Al intermetallic compounds and ε-Cu phase are obtained, resulting in excellent hardness uniformity and mirror polishability (roughness Ra 0.010~0.020μm after polishing with 12000 mesh). It is widely used in the plastic product industry where surface finish requirements are high. However, there are also some drawbacks. On the one hand, the high Al content in the steel leads to a high content of alumina inclusions, which in turn affects polishing performance. On the other hand, the high Ni, Cu, and Mo content significantly increases the alloy cost.

[0003] Chinese Patent No. CN200610117014.7 discloses "A copper age-hardening bainitic large-section plastic mold steel and its manufacturing process," with the following composition (wt%): C 0.08~0.18%, Si 0.15~0.50%, Mn 1.2~2.0%, V 0.05~0.20%, Cr 1.2~1.9%, Mo 0.15~0.50%, P ≤0.02%, S ≤0.01%, Ni 1.2~2.0%, Cu 0.50~1.0%, N ≤0.01%, Ti 0.005~0.025%, Ca 0~0.0050%, Al 0.01~0.04%. The manufacturing process involves direct air cooling after hot working, followed by tempering at 450~600°C, resulting in a finished product hardness of HRC37~43. Although the Ni and Al content was reduced, the invention still required the addition of a high amount of Mo, resulting in high alloy costs.

[0004] Chinese Patent No. CN201910756105.2 discloses a "production process for a high-mirror-finish plastic mold steel 1Ni3MnCuMoAl thick plate", with the following composition: C 0.10~0.20%, Si ≤0.45%, Mn 1.40~2.00%, Ni 2.90~3.40%, Mo 0.20~0.50%, Cu 0.80~1.20%, Al 0.70~1.20%, P≤0.015%, S≤0.005%. After smelting, casting, and rolling, the plate is solution-treated at 850±5℃, air-cooled after removal from the furnace, and finally aged at 520±20℃. The underlying principle is still based on a high-Ni, high-Al composition design, strengthening through the precipitation of Ni3Al intermetallic compounds and ε-Cu phase.

[0005] Chinese patent CN201810237986.2 discloses a "10Ni3MnCuAl-ESR age-hardening plastic mold steel" with the following composition: C 0.10-0.20%, Si 0.23-0.38%, Ni 2.5-3.5%, Mn 0.08-1.70%, Mo 0.16-0.34%, Cu 0.5-1.8%, Al 0.08-1.2%, P 0.01-0.02%, and S ≤0.005%. The solution treatment temperature is 820-880℃, air-cooled; the aging treatment temperature is 500-550℃, air-cooled. The design concept is based on a high Ni and high Al composition, strengthening the steel through the precipitation of Ni3Al intermetallic compounds and ε-Cu phase.

[0006] Chinese patent CN201710204791.3 discloses "a precipitation-hardening plastic mold steel and its preparation method," with the following composition: C 0.08–0.25%, Si 0.8–1.5%, S ≤0.030%, P ≤0.030%, Mn 0.4–0.8%, Ni 2.0–4.0%, Mo 0–1.5%, Cr 1.0–2.8%, Cu 0.5–1.5%, Al 0.5–2.0%, V 0–0.2%. After forging, it is held at 900–1000℃, slowly cooled to 650℃ and held thereafter, and then furnace-cooled to below 400℃ before being unloaded. This invention also uses a high-Ni, high-Al composition, strengthening through Ni3Al intermetallic compounds and ε-Cu phase precipitation, and utilizing higher Mo levels to improve corrosion resistance, but at a higher cost.

[0007] Chinese Patent No. CN201510358546.9 discloses "Anti-cavitation age-hardening high-gloss plastic mold steel and its preparation method". The composition is designed as follows: C ≤0.15%, Si 0.70~1.30%, Mn 0.40~1.00%, Ni 2.00~4.00%, Cr 3.00~5.00%, Mo≤1.0%, Cu ≤1.00%, Al≤1.50%, P≤0.010%, S≤0.005%. The solution is uniformly heated and held at 900~960℃, and then oil-cooled or mist-cooled to 80~150℃ after being removed from the furnace. It is then immediately placed in a tempering heat treatment furnace and held at 250±50℃ for 5h. Then, the temperature is increased to 500~550℃ at ≤80℃ / h for uniform and heat-held aging treatment, and finally air-cooled after being removed from the furnace. This invention is also designed with a high Ni and high Al composition, which is strengthened by Ni3Al intermetallic compounds and ε-Cu phase precipitation, and the corrosion resistance is improved by a higher Mo element, resulting in a higher cost.

[0008] In summary, the age-hardening plastic mold steels disclosed in the aforementioned patents still contain high levels of elements such as Mo, Ni, and Al. This not only increases the alloy cost but also, due to the addition of Al, easily leads to the formation of alumina and aluminum nitride inclusions. These inclusions are easily peeled off during polishing and can scratch the substrate. Furthermore, the manufacturing processes all involve solution treatment followed by aging. Therefore, there is an urgent need to develop plastic mold steels with lower alloy and processing costs that can meet the optical-grade, ultra-high precision requirements of aerospace, medical, and precision electronics fields. Summary of the Invention

[0009] The purpose of this invention is to provide a carbide-free precipitation-hardening bainitic plastic mold steel and its manufacturing method. The microstructure of the mold steel is bainite + ε-Cu copper-rich phase, with a tensile strength ≥1100MPa, a finished product hardness of 37~43HRC, a hardness difference of ≤2HRC between sections of 15~300mm thick steel plates, a polished roughness Ra≤0.010μm with 12000 mesh, and inclusions of Class B ≤1.0 according to GB / T10561-2023 standard. In addition, this invention does not require complex heat treatment processes and has high production efficiency. The mold steel can be applied in aerospace, medical, and precision electronics fields with optical-grade and ultra-high precision requirements.

[0010] To achieve the above objectives, the technical solution of the present invention is as follows: A carbide-free precipitation-hardening bainitic plastic mold steel, with the following chemical composition by mass percentage: C: 0.05~0.15%, Si: 0.25~1.0%, Mn: 0.8~2.0%, P≤0.040%, S≤0.020%, Cr: 2.5~5.0%, Ni: 0.8~2.0%, Cu: 1.0~3.0%, Al < 0.010%, The balance consists of Fe and other unavoidable impurities, and the following relationship must be satisfied simultaneously: Age hardening index (AHI): 12 ≤ AHI ≤ 20 AHI=20×[C]+5×[Cu]+[Cr]+0.8×[Mn]-0.5×[Ni]; Cu precipitation index Cupi ≥ 0.9, Cupi = [Cu] - 0.01 × [Mn] - 0.02 × [Ni]; No carbide precipitation was observed in the microstructure of the mold steel.

[0011] The component data in the above formulas are calculated as percentages. For example, if the carbon content is 0.10%, you can substitute 0.10 into [C] when calculating the formula.

[0012] Furthermore, the chemical composition of the mold steel also includes one or more of the following: V < 0.05%, Ca: 0.0005~0.0050%, and Mo < 0.10%, by mass percentage.

[0013] The microstructure of the mold steel described in this invention is bainite + ε-Cu copper-rich phase, and according to GB / T 10561-2023 standard, the inclusions of Class B are ≤1.0 grade.

[0014] The mold steel described in this invention has a tensile strength ≥1100MPa, a finished product hardness of 37~43HRC, a cross-sectional hardness difference of 15~300mm thick steel plate ≤2HRC, and a polishing roughness Ra≤0.010μm of 12000 mesh.

[0015] In the composition design of the mold steel described in this invention: Carbon (C) enhances the hardness and strength of steel through solid solution strengthening and carbide formation. As carbon content increases, the strength, hardness, and wear resistance of steel improve, but plasticity and toughness decrease accordingly. Furthermore, carbon combines with alloying elements such as chromium, molybdenum, and vanadium to form various carbides; the precipitation of large amounts of carbides can cause pitting after polishing. This invention controls the C content to 0.05~0.15%, using a low-carbon design to prevent carbide precipitation, further improving plasticity, toughness, and polishing performance.

[0016] Silicon (Si) can reduce the diffusion rate of carbon in ferrite, delay the precipitation and aggregation of carbides, and increase tempering stability. It also promotes the formation of a SiO2 film on the surface, improving the steel's oxidation resistance at high temperatures. However, excessive silicon content significantly reduces the plasticity and toughness of the steel, easily leading to banded structures, increasing decarburization sensitivity, and reducing weldability. Therefore, this invention controls the Si content to be 0.25~1.0%.

[0017] Manganese (Mn) is one of the elements that most significantly improves the hardenability of steel, effectively reducing the critical cooling rate and making it easier for steel to obtain a martensitic structure. Manganese has a greater affinity for sulfur than iron, forming high-melting-point MnS, thereby mitigating the harmful effects of sulfur on steel and improving machinability. Therefore, this invention controls the Mn content to be 0.8%~2.0%.

[0018] Chromium (Cr) significantly improves the hardenability of steel, enabling uniform microstructure even in large-section dies, while also enhancing oxidation and corrosion resistance. Secondly, during aging treatment, Cr hinders bainite boundary migration and suppresses matrix microstructure recovery; premature matrix softening negates the contribution of precipitation hardening. Cr maintains matrix microstructure stability, allowing the strengthening effect of Cu-rich precipitation to be fully realized. Furthermore, Cr can moderately reduce the equilibrium solid solubility of Cu in the matrix, expanding the driving force for aging precipitation, increasing bainite dislocation density, and creating more Cu nucleation sites, which is beneficial for achieving higher aging hardness with the same Cu content. Therefore, this invention controls the Cr content to be 2.5–5.0%.

[0019] This invention innovatively limits the Ni content to 0.8-2.0%. When Ni < 0.8%, the bainite laths are coarse, resulting in decreased impact toughness; above 0.8%, it significantly refines the bainite laths, balancing strength and toughness. It promotes the uniform precipitation of nano-rich Cu phases during low-temperature aging, improving precipitation strengthening efficiency. However, Cu steel precipitates are coarse and have poor toughness; Ni can refine the size of the Cu-rich precipitates. When Ni > 2.0%, there is an excess of residual austenite, and the aging hardness cannot reach above 37 HRC, failing to meet the requirements for high-quality production molds. Furthermore, this invention utilizes the nickel element naturally present in laterite nickel ore, significantly reducing alloy costs.

[0020] Copper (Cu) effectively enhances the corrosion resistance of plastic mold steel in acidic environments, which is particularly important for molds processing corrosive plastics containing fluorine and chlorine. The addition of copper significantly improves the machinability of plastic mold steel, which is crucial for mold manufacturing. During aging, supersaturated copper precipitates nanoscale copper-rich phases (ε-Cu) from the matrix. These precipitates produce a strong dispersion strengthening effect, significantly improving the hardness and strength of the steel. This invention designs a copper content of 1.0–3.0% to replace traditional Ni3Al precipitate strengthening. When Cu < 1.0%, the number of precipitates is insufficient, resulting in poor hardening; when Cu > 3.0%, copper tends to segregate into low-melting-point single-phase copper during continuous casting, causing the mold steel to form liquid copper and crack during hot rolling.

[0021] The present invention may also selectively add one or more of V≤0.2%, Ca:0.0005~0.0050%, and Mo≤0.2%, by mass percentage, as required by the specific characteristics.

[0022] V is a ferrite-forming element. Excessive V content is detrimental to the stability of the austenite structure, necessitating upper limit control of V. V easily forms VN or VC precipitates, impairing polishing performance. Since smelting technology cannot completely eliminate V, this invention controls the V content to no more than 0.05% to eliminate VN or VC precipitates. Therefore, this invention controls the V content to <0.05%.

[0023] Trace amounts of calcium (Ca) in steel primarily function to modify inclusions during steelmaking, transforming hard, poorly ductile inclusions into inclusions with good ductility. Inclusions with good ductility have a smaller impact on polishing performance compared to hard inclusions. Therefore, this invention controls the Ca content to 0.0005~0.0050%.

[0024] A small amount of Mo can inhibit the transformation from austenite to pearlite, significantly improve the hardenability of steel, and enhance corrosion resistance when combined with chromium.

[0025] In this invention, Al is considered an unavoidable impurity element. While Al helps deoxidize molten steel, it inevitably forms hard inclusions such as aluminum nitride and aluminum oxide. These inclusions may detach during mold polishing, scratching the mold steel and affecting the polishing process. If the size of these hard inclusions is large, they can also create polishing pits, affecting the surface quality of the plastic workpiece. Therefore, this invention controls Al < 0.010.

[0026] The innovative design of the carbide-free precipitation-hardening bainitic plastic mold steel of this invention lies in: 1. This invention employs a carbide-free bainitic matrix + ε-Cu copper-rich phase precipitation strengthening system, replacing the traditional Ni3Al strengthening route. Table 1 shows a comparison of the main chemical compositions of this invention with other patents. Compared to other schemes, this invention significantly reduces the Ni and Mo alloy content and eliminates the addition of Al. First, by replacing Mo with Cr and Mn, the hardenability of the material can be maintained, ensuring a uniform bainitic structure across the entire thickness section. Second, eliminating Al avoids alumina inclusions, improving polishing performance, and significantly reduces costs. Finally, this invention strictly limits carbon to a low carbon range of 0.05~0.15%, suppressing the precipitation of chromium and iron carbides at the source. Abandoning the Ni3Al intermetallic compound and ε-Cu copper-rich phase strengthening scheme for NAK80 type mold steel, this invention utilizes only age-induced precipitation of nano-ε-Cu copper-rich phase to achieve dispersion precipitation hardening. Ni refines the Cu-rich precipitates, improving the shortcomings of coarse Cu precipitation and insufficient toughness; at the same time, Cr increases the dislocation density of the matrix, provides nucleation sites for Cu-rich phases, and stabilizes the bainitic lath structure, ensuring that the precipitation strengthening effect is fully realized.

[0027]

[0028] 2. Develop the Age Hardening Index (AHI) to achieve uniform and controllable hardness in large cross-sections. This invention abandons the limitations of traditional mold steel hardness empirical formulas based solely on solid solution elements. It innovatively proposes a precipitation hardening potential index coupled with a composition constraint system, incorporating the precipitation hardening element Cu into the quantitative composition correlation formula, and establishing a two-dimensional composition matching mechanism for matrix solid solution strengthening and nanoprecipitation strengthening.

[0029] This invention constructs an age hardening index AHI: 12≤AHI≤20, AHI=20×[C]+5×[Cu]+[Cr]+0.8×[Mn]-0.5×[Ni]. Products with the target hardness range can be obtained within this range. In this index, C acts as a matrix solid solution strengthening and phase transformation regulator, which can significantly improve hardness; Cu can form ε-Cu copper-rich phase, bringing age hardening gains; Cr is used to regulate hardenability, provide solid solution strengthening and promote the precipitation of ε-Cu copper-rich phase; Mn also improves hardenability, but slightly inhibits the precipitation of ε-Cu copper-rich phase, so its hardening effect is lower than that of Cr; Ni inhibits the precipitation of ε-Cu copper-rich phase and also promotes austenite stability and inhibits bainite transformation, thereby weakening the negative effect of overall strengthening potential. When the index is below 12, the overall strengthening potential is insufficient, the number of aging precipitates is too small, and the hardness of the finished product cannot meet the minimum use requirement of 37HRC for precision molds; when the index is above 20, the superposition of solid solution strengthening and precipitation strengthening is too high, the material hardness exceeds the standard, the toughness decreases significantly, the mold is prone to chipping and cracking, and the polishing quality deteriorates.

[0030] 3. Develop a Cu precipitation index (CuPI) to achieve uniform precipitation of nanoscale ε-Cu rich copper phase. After hot rolling, the substrate hardness is approximately 33-37 HRC. To achieve a hardness of 37-43 HRC after age hardening, this invention uses thermodynamic calculations to determine the effects of various alloying elements on the precipitation temperature and content of the ε-Cu rich copper phase. Mn and Ni slightly increase the solid solubility of Cu in the matrix, thus mildly inhibiting the precipitation of the ε-Cu rich copper phase.

[0031] Based on experimental data and thermodynamic calculations, the Cu precipitation index Cupi = [Cu] - 0.01 × [Mn] - 0.02 × [Ni] was obtained. When Cupi ≥ 0.9, the matrix has sufficient effective Cu supersaturation, allowing a sufficient number of dispersed and fine ε-Cu copper-rich phases to precipitate during aging. This hinders dislocation movement through coherent strain strengthening, which can increase the hardness by approximately 4~6 HRC. If Cupi < 0.9, due to the solid solution binding of Mn and Ni, the effective Cu supersaturation inside the alloy is insufficient, resulting in a low content of ε-Cu copper-rich phases, large phase size, and poor dispersion. This limits the precipitation hardening effect and leads to insufficient hardness.

[0032] The method for manufacturing carbide-free precipitation-hardening bainitic plastic mold steel according to the present invention includes the following steps: 1) Smelting and casting Laterite nickel ore is smelted into nickel-iron molten iron and molten scrap iron is used as steelmaking mother liquor. Copper plates are added in an AOD furnace to adjust the alloy composition, and the steel is refined in an LF furnace to obtain the steel with the composition of the mold steel. Then, it is continuously cast into slabs at a casting speed of 0.8~1.2m / min. 2) Hot-rolled The continuously cast slab undergoes heating and heat preservation, descaling, and hot rolling; the slab heating temperature is 1200~1300℃, the heating time is 180~240min, and the final rolling temperature is 850~1000℃. 3) Cooling After hot rolling, the steel plate is cooled by water mist on the conveyor rollers at a rate of 1~5℃ / s to cool the steel plate temperature to 600~750℃. Then it is straightened by a hot straightener and then cooled off the conveyor rollers at a temperature of 500~600℃. 4) Stacking hardening over time The steel plates that come off the production line are immediately stacked one by one, and the temperature of the steel plates during stacking is T. d The temperature is 480~600℃. The steel plates are placed in a pit or enclosure, and the surface of the stacked steel plates is covered with insulation cotton, so that the stacked steel plates are slowly cooled to room temperature at a cooling rate S1 of 10~20℃ / h.

[0033] The present invention also provides a method for manufacturing a carbide-free precipitation-hardening bainitic plastic mold steel, comprising the following steps: 1) Smelting and casting Laterite nickel ore is smelted into nickel-iron molten iron and molten scrap iron is used as steelmaking mother liquor. Copper plates are added in an AOD furnace to adjust the alloy composition, and the steel is refined in an LF furnace to obtain the steel with the composition of the mold steel. Then, it is continuously cast into slabs at a casting speed of 0.8~1.2m / min. 2) Hot-rolled The continuously cast slab undergoes heating and heat preservation, descaling, and hot rolling; the slab heating temperature is 1200~1300℃, the heating time is 180~240min, and the final rolling temperature is 850~1000℃. 3) Cooling After hot rolling, the steel plate is cooled by water mist on the conveyor rollers at a rate of 1~5℃ / s to cool the steel plate temperature to 600~750℃. Then it is straightened by a hot straightener and then cooled by conveyor rollers at a temperature of 300~450℃. 4) Tempering and aging hardening First, steel plates with an offline temperature T2 of 300~450℃ are stacked one by one and placed in a pit or enclosure. The surface of the stacked steel plates is covered with insulation cotton, and the stacked steel plates are slowly cooled to room temperature at a cooling rate S2 of 10~20℃ / h. Second, the steel plates are placed in a tempering heat treatment furnace and heated from room temperature to 480~550℃ at a heating rate of 40~80℃ / h. Then, they are held at this temperature for 2~6 hours to complete the aging hardening treatment. Subsequently, they are cooled to the furnace exit temperature T3 of 250~350℃ at a cooling rate of 40~60℃ / h. Finally, the steel plates are removed from the tempering heat treatment furnace and air-cooled to room temperature.

[0034] In the manufacturing method described in this invention: Step 1) During the steelmaking process, copper plates are added during the AOD furnace refining stage. The resulting molten steel is then passed through an LF furnace to adjust the C and N content and remove inclusions. The casting speed is controlled at 0.8~1.2 m / min. Too low a speed will lead to low production efficiency, while too high a speed can easily cause defects such as segregation, porosity, and cracks inside the slab, resulting in uneven hardness and abnormal flaw detection. This casting speed range can stably obtain qualified slabs with dense structure and low segregation, providing high-quality billets for subsequent hot rolling.

[0035] Step 2) During hot rolling, the slab is heated to 1200~1300℃ and held for 180~240min. High-temperature heating provides kinetic conditions for the diffusion of alloying elements, improves the interdendritic element segregation caused by continuous casting, and achieves compositional homogenization. If the temperature is below 1200℃, the diffusion kinetics of alloying elements are insufficient, and segregation is difficult to eliminate; if it is above 1300℃, it is easy to cause grain coarsening or even overheating, which deteriorates the toughness of the steel. Insufficient holding time results in inadequate homogenization, while excessive holding time causes continuous grain coarsening, which can easily lead to surface cracks. The final rolling temperature is 850~1000℃, which is in the austenite stable region. The rolling deformation refines the austenite grains, creating conditions for the subsequent formation of fine-grained carbide-free bainite; if the final rolling temperature is too high, the austenite recrystallization is sufficient, and the grains are coarse; if the final rolling temperature is too low, it enters the two-phase region for rolling, and the deformation resistance increases sharply, which not only easily produces surface crack defects, but also leads to the appearance of banded structures, exacerbating the anisotropy of properties.

[0036] Step 3) During the cooling process, the water mist cooling rate after hot rolling is 1~5℃ / s, cooling to 600~750℃: precisely avoiding the high-temperature pearlite phase transformation range, inhibiting the formation of ferrite and pearlite; if the cooling rate is below 1℃ / s, pearlite is easily precipitated, resulting in insufficient hardness and poor polishability; if the cooling rate is above 5℃ / s, the surface cooling is too fast, the temperature difference between the surface and the core is too large, inducing huge internal stress, and at the same time, it is easy to form surface martensite. Hot straightening is carried out at 600~750℃. At high temperatures, the strength of the steel plate is lower, the straightening resistance is smaller, which can effectively eliminate hot rolling warping and avoid residual stress and microcracks generated by low-temperature straightening.

[0037] Step 4) During the aging hardening process, the present invention sets up two process paths for aging hardening, taking into account both high-efficiency mass production and high-precision performance control.

[0038] The first method is the stacking aging process (natural stacking and slow cooling): high-temperature steel plates that have been removed from the production line at 500~600℃ are stacked one by one, covered with insulation cotton, and slowly cooled to room temperature at an extremely low rate of 10~20℃ / h. This process relies on the residual heat of the steel plates to achieve self-aging, requiring no additional heating equipment, resulting in extremely low energy consumption and a simple production process. The extremely low slow cooling rate ensures that the overall temperature of the steel plates decreases uniformly, without internal or external temperature difference stress, while providing sufficient diffusion time for supersaturated Cu atoms in the matrix, promoting the uniform and dispersed precipitation of nano-ε-Cu copper-rich phase, and simultaneously completing microstructure stabilization and precipitation strengthening, as shown in the metallographic microstructure photograph in Example 1. Figure 2 As shown, all are bainitic structures with ε-Cu copper-rich phases such as... Figure 3As shown in the image, the SEM image reveals localized Cu enrichment after aging, forming a copper-rich ε-Cu precipitate. This test result corroborates the Cu precipitation index (CuPI) in terms of composition, proving that the alloy can undergo Cu precipitation and precipitation hardening. This process achieves self-aging hardening of a carbide-free bainitic matrix, making it suitable for mass production of conventional precision mold steels. The products produced by this process have uniform hardness, excellent polishing performance, eliminate the need for prolonged tempering and aging, have low production costs, and significantly reduce carbon emissions from the process.

[0039] The second method is tempering aging process (tempering heat treatment furnace): For steel plates cooled to room temperature after rolling at 300~450℃, a segmented temperature-controlled tempering aging process is used in a tempering heat treatment furnace. First, the residual heat at 300~450℃ after rolling is used for heat preservation and stacking to achieve residual heat pre-enrichment treatment: promoting the segregation of Cu atoms to form a large number of precipitation precursors, significantly increasing the nucleation density of Cu-rich nano-phase in the subsequent aging stage; simultaneously releasing hot rolling stress, improving the flatness of the plate, and adapting to the high polishing requirements of plastic molds. Second, the temperature is increased at a rate of 40~80℃ / h to 480~550℃: slow heating avoids large temperature differences in different parts of the steel plate, preventing deformation induced by local thermal stress. Too rapid heating can easily cause temperature unevenness between the plate surface and core, and between the width edge and the middle, resulting in asynchronous precipitation of nano-ε-Cu copper-rich phase and increased hardness fluctuations. Too slow heating reduces production efficiency. Secondly, 480~550℃ is the suitable precipitation range for nano-ε-Cu copper-rich phase. If the tempering and aging temperature is too low, the precipitation kinetics are insufficient and the hardening effect is weak. If the temperature is too high, it will lead to coarsening of the nano-ε-Cu copper-rich phase and bainite laths, deterioration of toughness, and reduction of polishing performance. Finally, a tempering and aging holding time of 2~6h can ensure sufficient diffusion of Cu atoms to form a uniformly dispersed nano-ε-Cu copper-rich phase, as shown in Example 5. Figure 4 As shown, the ε-Cu copper-rich phase is small in size (≤200nm) and is very uniformly distributed in the bainitic structure, stably achieving a target hardness of 37~43HRC.

[0040] After heat treatment, the steel is cooled to 250-350℃ at a rate of 40-60℃ / h before being removed from the furnace. This controlled cooling rate suppresses rapid microstructural transformation during aging, preventing rapid coarsening of precipitates. Cooling to 250-350℃ eliminates the need for furnace cooling to room temperature, balancing dimensional stability and production efficiency. Residual stress levels are low within this temperature range, and air cooling after removal from the furnace does not result in significant deformation, ultimately achieving low internal stress, uniform hardness, and stable microstructure in the steel. Segmented temperature control suppresses coarsening of precipitates and promotes microstructural softening, significantly reducing residual stress in the plate and ensuring uniform cross-sectional hardness and extremely high dimensional accuracy for thick plates. This makes it suitable for the performance requirements of precision molds in ultra-mirror finish, ultra-high precision, and long-life corrosion conditions.

[0041] The optimal precipitation temperature range for the ε-Cu copper-rich phase described in this invention is 450~550℃. However, the stack cooling process has no additional heat source and relies on residual heat for natural cooling. To ensure a holding time (more than 2 hours) within the 450~550℃ temperature range, the stack cooling temperature needs to be increased by 30~50℃ compared to the optimal precipitation temperature range (450~550℃). However, the stack cooling temperature should not exceed 600℃; otherwise, at this stack cooling rate, a full bainite structure cannot be formed, resulting in a large amount of ferrite and a significant reduction in hardness. The tempering aging process, on the other hand, has a stable heat input and is heat-stable. It only requires holding at the optimal precipitation temperature range (450~550℃) for 2~6 hours, but the holding time should not exceed 6 hours; otherwise, it will also lead to the elimination of dislocations in the bainite, resulting in insufficient hardness.

[0042] In summary, the preparation process described in this invention innovatively integrates low-cost smelting, precise phase transformation cooling, and a dual-mode process of stacking aging and tempering aging, abandoning the complex process of high-energy-consuming isothermal quenching and repeated heat treatment of traditional bainitic mold steel. Cost reduction and efficiency improvement are achieved through laterite nickel ore batching, and the phase transformation process is precisely controlled by segmented cooling to eliminate carbide and abnormal structure formation at the source, resulting in carbide-free bainite and ε-Cu-rich copper phase microstructure. Combined with a dual-mode aging hardening system, low-cost mass production can be achieved through slow cooling using residual heat stacking, while high-precision control of performance can be achieved through precise control of the tempering aging process in a tempering heat treatment furnace. Through low-carbon and extremely low-alumina composition design, high-temperature mist cooling, and tempering aging temperature design, carbide and alumina inclusions are avoided, resulting in ultra-mirror polishing properties. By increasing chromium and copper content and suppressing carbide precipitation, pitting corrosion resistance is further improved compared to traditional mold steels such as NAK80. By employing a carbide-free and bainitic microstructure design, the strength and toughness are significantly improved compared to martensitic mold steel. Through controlled stacking cooling and tempering heating and cooling rates, stress is effectively released and the microstructure stabilized, resulting in excellent dimensional stability. This invention is perfectly suited to the industrial production needs of various corrosive plastics and optical precision injection molds.

[0043] The innovation of the manufacturing method described in this invention lies in: 1. Precise control of controlled cooling phase transformation process, resulting in a bainitic microstructure free of carbides.

[0044] Traditional bainitic steel relies on a high-energy-consuming and complex process involving isothermal quenching in a salt bath and forced temperature-controlled phase transformation. In contrast, this invention employs a segmented phase transformation control technology: precise water mist cooling after hot rolling, high-temperature hot straightening, and controlled online cooling at medium temperature. By limiting the cooling rate to 1~5℃ / s, the abnormal phase transformation range of pearlite and martensite is avoided. No additional quenching heat treatment is required throughout the process, resulting in a carbide-free, uniform bainitic matrix. This effectively solves the problems of uneven microstructure, easy carbide precipitation, and uneven hardness in large cross-sections associated with traditional processes, simplifying the production process and reducing heat treatment energy consumption.

[0045] 2. Dual-mode age hardening adaptation process, balancing mass production efficiency and precision performance.

[0046] Conventional precipitation-hardening plastic mold steels rely on long-term tempering and aging treatment to precipitate Ni3Al and ε-Cu copper-rich phases, which is a complex process and has high alloy costs.

[0047] This invention innovatively sets up a dual-process system of stacking aging (stacking slow cooling residual heat self-aging) and tempering aging (tempering heat treatment furnace) to adapt to different production and operating conditions. Utilizing the residual heat from steel plate rolling to achieve low-temperature slow cooling self-aging promotes uniform and dispersed precipitation of nano-Cu-rich phases, completing precipitation strengthening without the need for additional heating processes, resulting in low energy consumption and high mass production efficiency. Simultaneously, the tempering aging process, precisely controlled by the tempering heat treatment furnace, allows for precise regulation of the precipitation kinetics of nano-Cu-rich phases, significantly reducing residual stress and heat treatment deformation in the plate. The flexible switching between the two modes solves the industry problems of traditional precipitation-hardening die steels, such as limited performance control, insufficient precision, and poor mass production stability.

[0048] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention employs a low-carbon (C: 0.05~0.15%) and extremely low-vanadium (V < 0.05%) composition design. This suppresses carbide precipitation at its source, and the water mist cooling process after hot rolling further inhibits carbide precipitation at high temperatures. This eliminates the micro-galvanic corrosion source formed by carbides and the matrix, and also eliminates the negative impact of carbides causing a decrease in polishing performance.

[0049] 2. This invention employs a high-chromium (Cr: 2.5~5.0%) composition design. This high-chromium composition design constructs a chromium-rich surface passivation film, significantly improving the pitting corrosion resistance of mold steel under corrosive plastic molding conditions containing chlorine and organic acids. This effectively solves the defects of traditional mold steel being prone to pitting and pitting of plastic parts. Furthermore, Cr also plays a novel role as a "Cu precipitation regulator," appropriately reducing the equilibrium solid solubility of Cu in the matrix, increasing the driving force for aging precipitation, and providing precipitation sites for ε-Cu copper-rich phases.

[0050] 3. This invention employs an extremely low aluminum (Al < 0.010%) composition design and modifies inclusions using Ca. Traditional aluminum precipitation-hardening mold steels, due to the large amount of aluminum added, easily form hard alumina inclusions, which can easily scratch the matrix during polishing. The extremely low aluminum composition design of this invention avoids this negative impact. Due to limitations in smelting technology, a very small amount of Al is unavoidable in the alloy composition. Research shows that when Al < 0.010%, large particles of alumina and aluminum nitride inclusions are not formed, thus not affecting polishing performance. Furthermore, Ca (0.0005~0.0050%) is used to modify the hard, poorly ductile inclusions into inclusions with good ductility. Inclusions with good ductility have less impact on polishing performance compared to hard inclusions. This results in excellent mirror polishing performance, with a polishing roughness Ra ≤ 0.010 μm at 12000 grit, meeting the molding requirements of optical-grade, ultra-high-precision plastic parts.

[0051] 4. This invention breaks through the high-cost bottleneck of high-end precision mold steel. It uses laterite nickel ore molten nickel-iron mixed with scrap iron as the smelting mother liquor, and utilizes the laterite nickel ore to smelt the liquid nickel-iron for hot steelmaking, eliminating the intermediate process of electrolytic nickel preparation and significantly reducing the cost of nickel alloying raw materials. At the same time, laterite nickel ore naturally contains associated alloying elements such as Cr and Mn, reducing the amount of chromium and manganese alloys added. The alloying elements in the liquid nickel-iron mother liquor are evenly distributed with lower element segregation, facilitating precise control of element ratios. The innovative design incorporates a dual-process system of stacking aging and tempering aging, abandoning the high-energy-consuming and complex process of multiple heat treatments in traditional mold steel production. It can achieve low-energy-consumption mass production by relying on the residual heat of rolling, and can also achieve customized production of high-performance precision plates through precise temperature-controlled aging.

[0052] 5. The steel of this invention can meet the stringent requirements of optical, aerospace, medical and precision electronics fields for mold steel to have "ultra-mirror finish, high strength, high uniformity and long life".

[0053] In terms of optical applications, this invention adopts an extremely low aluminum (Al < 0.010%) design and constructs a carbide-free bainitic structure, with B-type inclusions ≤ 1.0 grade, eliminating hard inclusions such as alumina and aluminum nitride from the source and preventing them from peeling off and scratching the substrate during polishing. After polishing with 12000 grit, the surface roughness Ra ≤ 0.010 μm achieves an optical-grade mirror effect, which can meet the molding requirements of optical-grade and ultra-high appearance precision plastic parts.

[0054] In high-reliability applications such as aerospace, steel combines tensile strength ≥1100MPa, finished hardness 37~43HRC, and the excellent toughness of bainitic structure. Combined with the pitting resistance provided by a chromium-rich passivation film, it maintains performance and dimensional stability even under harsh corrosive conditions such as those containing chlorine, organic acids, and humid atmospheres. This makes it suitable for precision molds with extremely high requirements for service life and reliability. Furthermore, the cross-sectional hardness difference of 15~300mm thick steel plates is ≤2HRC, ensuring uniform hardness, high dimensional accuracy, and good consistency of molded parts in large molds. Attached Figure Description

[0055] Figure 1 This is a process flow diagram of the hot rolling and heat treatment process of the plastic mold steel described in this invention; Figure 2 The image shows the metallographic structure of Example 1 (stack cooling aging) of the plastic mold steel described in this invention; Figure 3 Scanning electron microscope images and precipitates of the plastic mold steel of Example 1 (stack cooling aging) described in this invention; Figure 4 The image shows a scanning electron microscope (SEM) image and precipitated phase of Example 5 (tempering and aging) of the plastic mold steel described in this invention. Detailed Implementation

[0056] The present invention will be further described below with reference to the embodiments and accompanying drawings.

[0057] The chemical compositions of the embodiments and comparative examples of this invention are shown in Table 2, with the balance being Fe and other unavoidable impurity elements. The smelting, continuous casting, and hot rolling process parameters of the embodiments and comparative examples are shown in Table 3. The heat treatment aging process parameters of the embodiments and comparative examples are shown in Table 4. The tempering aging process parameters of the embodiments and comparative examples are shown in Table 5. The performance results of the embodiments and comparative examples are shown in Table 6.

[0058] Examples 1-9 are products manufactured according to the composition and process of this invention, and their performance meets the requirements. The process flow for the hot rolling and heat treatment procedures in these examples is as follows: Figure 1 .

[0059] See Figure 2 The image shown is a metallographic photograph of Example 1. It can be seen that all structures are bainitic, with ε-Cu copper-rich phases as shown. Figure 3 As shown in the image, the SEM image reveals that Cu enrichment occurs in localized areas after aging, forming a copper-rich ε-Cu precipitate. This test result corroborates the Cu precipitation index Cupi from a compositional perspective, proving that the alloy can undergo Cu precipitation and produce a precipitation hardening effect.

[0060] See Figure 4The image shows a scanning electron microscope (SEM) image and the precipitated phase after tempering and aging in Example 5. As can be seen from the image, tempering and aging ensures that Cu atoms diffuse sufficiently to form a uniformly dispersed nano-ε-Cu copper-rich phase. The ε-Cu copper-rich phase is small in size (≤200nm) and uniformly distributed in the bainitic structure, stably achieving a target hardness of 37~43HRC.

[0061] Compared with Examples 1-9, Comparative Example 1 has a Cu content of less than 1.0% and an age hardening index of 9.60, which is lower than the range of 12-20 for hardness index. As a result, the measured hardness value of this comparative example is only 36.1 HRC, which does not reach the design value.

[0062] Compared with Examples 1-9, Comparative Example 2 has a Cu content higher than 3.0% and an age hardening index of 22.3, which is higher than the range of 12-20 for hardness index. As a result, the measured hardness value of this comparative example is 44.6 HRC, which exceeds the design value.

[0063] Compared with Examples 1-4, Comparative Example 3 had a stack cooling temperature that was too low, resulting in insufficient residence time for the precipitated phase and failure to precipitate enough nano-ε-Cu copper-rich phase. As a result, the measured hardness value of this comparative example was only 35.8 HRC and the tensile strength was 1083 MPa, which did not reach the design value.

[0064] Compared with Examples 1-9, Comparative Example 4 showed that the water cooling rate after hot rolling was too fast, resulting in uneven hardness distribution and a maximum hardness difference of 2.3 HRC across the cross section.

[0065] Compared with Examples 5-9, Comparative Example 5 had a tempering and aging temperature that was too low, which prevented the precipitation of nano-ε-Cu copper-rich phase. As a result, the measured hardness value of this comparative example was only 35.7 HRC and the tensile strength was 1093 MPa, which did not reach the design value.

[0066] Compared with Examples 5-9, Comparative Example 6 had a shorter holding time during tempering and aging, resulting in a lower precipitation of nano-ε-Cu copper-rich phase. Consequently, the measured hardness of this comparative example was only 35.6 HRC and the tensile strength was 1096 MPa, which did not meet the design value.

[0067] Compared with Examples 5-9, Comparative Example 7 has a copper content of only 0.85% and a Cu precipitation index of 0.81, which is less than 1.0. The low amount of ε-Cu rich phase precipitation resulted in a measured hardness value of only 34.9 HRC and a tensile strength of 1060 MPa for this comparative example, which did not meet the design values.

[0068] Compared with Examples 1-9, Comparative Example 8 showed that the addition of 0.023% Al resulted in a Class B inclusion rating of 1.5 and a roughness Ra of 0.013 μm after polishing.

[0069] The above embodiments and comparative examples illustrate that qualified plastic mold steel products can be obtained according to the composition design and process parameters described in this invention.

[0070] The plastic mold steel of this invention has excellent mechanical properties: In the embodiment, the plastic mold steel obtained under the specified composition and process parameters has a bainitic structure + ε-Cu copper-rich phase, and B-type inclusions ≤ 1.0 grade; its tensile strength is ≥ 1100 MPa, the finished product hardness is 37~43 HRC, the hardness difference of the cross section of the 15~300 mm thick steel plate is ≤ 2 HRC, and the polishing roughness Ra of 12000 mesh is ≤ 0.010 μm.

[0071]

[0072]

[0073]

[0074]

[0075]

Claims

1. A carbide-free precipitation-hardening bainitic plastic mold steel, characterized in that, Its chemical composition by mass percentage is: C:0.05~0.15%, Si: 0.25~1.0%, Mn: 0.8~2.0%, P≤0.040%, S≤0.020%, Cr:2.5~5.0%, Ni: 0.8~2.0%, Cu: 1.0~3.0%, Al<0.010%, The balance consists of Fe and other unavoidable impurities, and the following relationship must be satisfied simultaneously: Age hardening index (AHI): 12 ≤ AHI ≤ 20 AHI =20×[C]+5×[Cu]+[Cr]+0.8×[Mn]-0.5×[Ni]; Cu precipitation index Cupi ≥ 0.9, Cupi = [Cu] - 0.01 × [Mn] - 0.02 × [Ni]; No carbide precipitation was observed in the microstructure of the mold steel.

2. The carbide-free precipitation-hardening bainitic plastic mold steel as described in claim 1, characterized in that, The composition of the mold steel also includes one or more of the following: V < 0.05%, Ca: 0.0005~0.0050%, and Mo < 0.10%, by mass percentage.

3. The carbide-free precipitation-hardening bainitic plastic mold steel as described in claim 1 or 2, characterized in that, The microstructure of the mold steel is bainite + ε-Cu copper-rich phase, and according to GB / T 10561-2023 standard, the inclusions are of grade B ≤1.

0.

4. The carbide-free precipitation-hardening bainitic plastic mold steel as described in claim 1 or 2, characterized in that, The mold steel has a tensile strength ≥1100MPa, a finished product hardness of 37~43HRC, a cross-sectional hardness difference of 15~300mm thick steel plate ≤2HRC, and a polishing roughness Ra≤0.010μm of 12000 mesh.

5. The carbide-free precipitation-hardening bainitic plastic mold steel as described in claim 3, characterized in that, The mold steel has a tensile strength ≥1100MPa, a finished product hardness of 37~43HRC, a cross-sectional hardness difference of 15~300mm thick steel plate ≤2HRC, and a polishing roughness Ra≤0.010μm of 12000 mesh.

6. The method for manufacturing carbide-free precipitation-hardening bainitic plastic mold steel according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Smelting and casting Laterite nickel ore is smelted into nickel-iron molten iron and molten scrap iron is used as steelmaking mother liquor. Copper plates are added in an AOD furnace to adjust the alloy composition, and the steel is refined in an LF furnace to obtain the steel with the composition of the mold steel. Then, it is continuously cast into slabs at a casting speed of 0.8~1.2m / min. 2) Hot rolling The continuously cast slab undergoes heating and heat preservation, descaling, and hot rolling; the slab heating temperature is 1200~1300℃, the heating time is 180~240min, and the final rolling temperature is 850~1000℃. 3) Cooling After hot rolling, the steel plate is cooled by water mist on the conveyor rollers at a rate of 1~5℃ / s to cool the steel plate temperature to 600~750℃. Then it is straightened by a hot straightener and then cooled off the conveyor rollers at a temperature of 500~600℃. 4) Stacking hardening over time The steel plates that come off the production line are immediately stacked one by one, and the temperature of the steel plates during stacking is T. d The temperature is 480~600℃. The steel plates are placed in a pit or enclosure, and the surface of the stacked steel plates is covered with insulation cotton, so that the stacked steel plates are slowly cooled to room temperature at a cooling rate S1 of 10~20℃ / h.

7. The method for manufacturing carbide-free precipitation-hardening bainitic plastic mold steel according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Smelting and casting Laterite nickel ore is smelted into nickel-iron molten iron and molten scrap iron is used as steelmaking mother liquor. Copper plates are added in an AOD furnace to adjust the alloy composition, and the steel is refined in an LF furnace to obtain the steel with the composition of the mold steel. Then, it is continuously cast into slabs at a casting speed of 0.8~1.2m / min. 2) Hot rolling The continuously cast slab undergoes heating and heat preservation, descaling, and hot rolling; the slab heating temperature is 1200~1300℃, the heating time is 180~240min, and the final rolling temperature is 850~1000℃. 3) Cooling After hot rolling, the steel plate is cooled by water mist on the conveyor rollers at a rate of 1~5℃ / s to cool the steel plate temperature to 600~750℃. Then it is straightened by a hot straightener and then cooled by conveyor rollers at a temperature of 300~450℃. 4) Tempering and aging hardening First, steel plates with an offline temperature T2 of 300~450℃ are stacked one by one and placed in a pit or enclosure. The surface of the stacked steel plates is covered with insulation cotton, and the stacked steel plates are slowly cooled to room temperature at a cooling rate S2 of 10~20℃ / h. Second, the steel plates are placed in a tempering heat treatment furnace and heated from room temperature to 480~550℃ at a heating rate of 40~80℃ / h. Then, they are held at this temperature for 2~6 hours to complete the aging hardening treatment. Subsequently, they are cooled to the furnace exit temperature T3 of 250~350℃ at a cooling rate of 40~60℃ / h. Finally, the steel plates are removed from the tempering heat treatment furnace and air-cooled to room temperature.

Citation Information

Patent Citations

  • Copper-ageing hardening bainite large-section plastic mould steel and manufacturing technique thereof

    CN101161850A

  • An anti-cavitation age-hardening high-gloss plastic mold steel and its preparation method

    CN105002433B

  • Precipitation hardening type plastic die steel and preparation method thereof

    CN106978564A

  • 10Ni3MnCuAl-ESR age hardening type plastic mold steel

    CN110295314A

  • Production process of high-mirror-finish plastic die steel 1Ni3MnCuMoAl thick plate

    CN110565014A